Sugar Signaling and Post-transcriptional Regulation in Plants: An Overlooked or an Emerging Topic? - Wang, Ming; Zang, Lili; Jiao, Fuchao; Perez-Garcia, Maria-Dolores; Ogé, Laurent; Hamama, Latifa; Le Gourrierec, José; Sakr, Soulaiman; Chen, Jingtang (Frontiers in Plant Science, 2020)
Plants are autotrophic organisms that self-produce sugars through photosynthesis. These sugars serve as an energy source, carbon skeletons, and signaling entities throughout plants’ life. Post-transcriptional regulation of gene expression plays an important role in various sugar-related processes. In cells, it is regulated by many factors, such as RNA-binding proteins, microRNAs, the spliceosome, etc. To date, most of the investigations into sugar-related gene expression have been focused on the transcriptional level in plants, while only a few studies have been conducted on post-transcriptional mechanisms. The present review provides an overview of the relationships between sugar and post-transcriptional regulation in plants. It addresses the relationships between sugar signaling and RNA-binding proteins, microRNAs and mRNA stability. These new items insights will help to reach a comprehensive understanding of the diversity of sugar signaling regulatory networks, and open onto new investigations into the relevance of these regulations for plant growth and development.